Th1/Th17 cell induction and corresponding reduction in ATP consumption following vaccination with the novel Mycobacterium tuberculosis vaccine MVA85A. - Kristin L Griffiths; Ansar A Pathan; Angela M Minassian; Clare R Sander; Natalie E R Beveridge; Adrian V S Hill; Helen A Fletcher; Helen McShane (PLoS ONE)
Vaccination with Bacille Calmette-Guérin (BCG) has traditionally been used for protection against disease caused by the bacterium Mycobacterium tuberculosis (M.tb). The efficacy of BCG, especially against pulmonary tuberculosis (TB) is variable. The best protection is conferred in temperate climates and there is close to zero protection in many tropical areas with a high prevalence of both tuberculous and non-tuberculous mycobacterial species. Although interferon (IFN)-γ is known to be important in protection against TB disease, data is emerging on a possible role for interleukin (IL)-17 as a key cytokine in both murine and bovine TB vaccine studies, as well as in humans. Modified Vaccinia virus Ankara expressing Antigen 85A (MVA85A) is a novel TB vaccine designed to enhance responses induced by BCG. Antigen-specific IFN-γ production has already been shown to peak one week post-MVA85A vaccination, and an inverse relationship between IL-17-producing cells and regulatory T cells expressing the ectonucleosidease CD39, which metabolises pro-inflammatory extracellular ATP has previously been described. This paper explores this relationship and finds that consumption of extracellular ATP by peripheral blood mononuclear cells from MVA85A-vaccinated subjects drops two weeks post-vaccination, corresponding to a drop in the percentage of a regulatory T cell subset expressing the ectonucleosidase CD39. Also at this time point, we report a peak in co-production of IL-17 and IFN-γ by CD4(+) T cells. These results suggest a relationship between extracellular ATP and effector responses and unveil a possible pathway that could be targeted during vaccine design.